Pelatihan Penulisan Kreatif Teks Eksplanasi dengan Model Picture and Picture di SMP Negeri Tublopo Melalui Gerakan Literasi Sekolah - Rejo, Uman; Siki, Ferdinandus (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The main purpose of this activity is to provide understanding, deepening of the discussion, and training to students of Tublopo State Junior High School in South Bikomi district of North Central Timor district in creative writing of explantation text effectively using picture and picture model through Gerakan Literasi Sekolah (GLS). This activity was held for 4 days, namely November 26, 2020, December 2, 2020, and December 11-12, 2020 in accordance with the schedule of implementation that has been set with partner teachers at Tublopo State Junior High School. This activity was attended by 15 students. There are 3 stages in this activity. In the preparatory stage, the team conducted observations to the school and communicated with the principal and teachers of Bahasa Indonesia subjects in this school. The second stage, the implementation stage in the form of the introduction and application of picture and picture models in the creative writing of explantation text that will be used by students. The third stage, evaluation of the implementation of activities that have been carried out based on the achievements that have been produced. Based on the activities that have been carried out, students are increasingly interested and skilled to produce creative explantation texts, especially those related to events or phenomena about nature, society, and culture. The model used was judged by students to be more effective and efficient. Although in its implementation, many obstacles are found. These constraints were found, particularly in writing language skills, grammar, and specific characteristics of explantation text. === Tujuan utama dari kegiatan ini adalah untuk memberikan pemahaman, pendalaman diskusi, dan pelatihan kepada siswa SMP Negeri Tublopo, Kecamatan Bikomi Selatan, Kabupaten Timor Tengah Utara dalam penulisan kreatif teks eksplanasi secara efektif dengan model gambar dan gambar melalui Gerakan Literasi. Sekolah (GLS). Kegiatan ini dilaksanakan selama 4 hari, yaitu 26 November 2020, 2 Desember 2020, dan 11—12 Desember 2020 sesuai dengan jadwal pelaksanaan yang telah ditetapkan bersama guru mitra di SMP Negeri Tublopo. Kegiatan ini diikuti oleh 15 siswa. Ada 3 tahapan dalam kegiatan ini. Pada tahap persiapan, tim melakukan observasi ke sekolah dan berkomunikasi dengan kepala sekolah dan guru mata pelajaran Bahasa Indonesia di sekolah ini. Tahap kedua, tahap implementasi berupa pengenalan dan penerapan model gambar dan gambar dalam penulisan kreatif teks eksplanasi yang akan digunakan oleh siswa. Tahap ketiga, evaluasi pelaksanaan kegiatan yang telah dilakukan berdasarkan capaian yang telah dihasilkan. Berdasarkan kegiatan yang telah dilakukan, siswa semakin tertarik dan terampil untuk menghasilkan teks eksplanasi kreatif, khususnya yang berkaitan dengan peristiwa atau fenomena tentang alam, masyarakat, dan budaya. Model yang digunakan dinilai oleh siswa lebih efektif dan efisien. Meski dalam pelaksanaannya banyak ditemukan kendala. Kendala-kendala tersebut ditemukan, terutama dalam keterampilan menulis bahasa, tata bahasa, dan ciri-ciri khusus teks eksplanasi.